Chain of Portable Health Folders: A Systematic Literature Review - Mateus, D.; Martins, A.; Correia, R. (8th EAI International Conference on Intelligent Transport Systems (INTSYS 2024)), 2024)
Abstract: The rise of Information Technologies’ influence during the 3rd industrial revolution led to the development of Digital Health Records, with Electronic Health Records (EHRs) and Personal Health Records (PHRs) be-ginning patient empowerment [1]. Today, Health Wallets (HWs), leveraging technologies like Fast Healthcare Interoperability Resources (FHIR) and Blockchain [2], represent the next step in this evolution, focusing on pa-tient-centric health management, and the growing needs of availability, transparency, and privacy and reliability. The paper, henceforth, will conduct a Systematic Literature Review, following the PRISMA framework [3], with the aim at exploring the characteristics of existing patient information plat-forms, advantages and limitations of their use, and gaps in the current solu-tions. An initial search yielded 850 articles, of which 36 were included in the analysis. The results show that healthcare professionals generally support the integration of HWs into practice [4], with accelerated research and imple-mentation following the Covid-19 pandemic. These platforms aim for secure data management, although challenges persist, particularly in terms of in-teroperability, and data protection [5]. Benefits include Patient empower-ment, better treatment, and cost reduction as well as operational efficiency. Despite some resistance due to established routines and patient eHealth liter-acy, key issues are mitigated by key technologies such as FHIR [6], Block-chain, Role Based Access Control (RBAC), and Bidirectional Communica-tion. Research should focus on the ability of Health Wallets to inte-grate seamlessly with existing systems to avoid additional complexity, en-hance privacy, enhance user experience, and improve healthcare efficiency.